MANAJEMEN PERKAWINAN DAN JUMLAH ANAK SEKELAHIRAN DI PETERNAKAN BABI CV. ADHI FARM KARANGANYAR - , THEO TRY YOSA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
writing this final project basically form activity fieldwork (PKL) in livestock swine Adhi Farm Karanganyar. Fieldwork activity implemented on date 31 march until 4 april 2014. Total number of population swine on livestock 1029 pigs. Objective write this final project is for understand breeding management and littersize on Adhi Farm. Data obtainable with observation and interview with employee and recording on livestock. Research was held to know how breeding management and littersize especially pigs between puberty, estrus cycle, estrus detection, breeding method, and littersize. Result form research on livestock taking data wench pigs are mating between age 7,5 untill 8 month, estrus cycle 21 days and the breeding was doing on first day and second day estrus cycle. Artificial insemination and nature. Estrus detection was held with monitoring the sowâs being estrus, will do behavior like : the sow looks nervous, screaming, and if to press brisket the sowâs will be quiet, appetite reduce, and gelatinous will out form vulva and get swelling. The boar has started mate between 1,5 old and individual cage. The data was take place litter size on Adhi Farm. The conclusion is breeding management by now going well, but will be right if Adhi Farm to be prepare for exercise cage pregnancy sow already.